Identification and characterisation of citrullinated antigen-specific B cells in peripheral blood of patients with rheumatoid arthritis. Issue 6 (1st June 2015) - Kerkman, Priscilla F; Fabre, Emeline; van der Voort, Ellen I H; Zaldumbide, Arnaud; Rombouts, Yoann; Rispens, Theo; Wolbink, Gertjan; Hoeben, Rob C; Spits, Hergen; Baeten, Dominique L P; Huizinga, Tom W J; Toes, René E M; et al.
Abstract : Objectives: Immunity to citrullinated antigens is a hallmark of rheumatoid arthritis (RA). We set out to elucidate its biology by identifying and characterising citrullinated antigen-specific B cells in peripheral blood of patients with RA. Methods: Differentially labelled streptavidin and extravidin tetramers were conjugated to biotinylated CCP2 or control antigens and used in flow cytometry to identify citrullinated antigen-specific B cells in peripheral blood. Tetramer-positive and tetramer-negative B cells were isolated by fluorescence activated cell sorting (FACS) followed by in vitro culture and analysis of culture supernatants for the presence of antibodies against citrullinated protein antigens (ACPA) by ELISA. Cells were phenotypically characterised by flow cytometry. Results: By combining differentially labelled CCP2 tetramers, we successfully separated citrullinated antigen-specific B cells from non-specific background signals. Isolated tetramer-positive B cells, but not tetramer-negative cells, produced large amounts of ACPA upon in vitro stimulation. Phenotypic analyses revealed that citrullinated antigen-specific B cells displayed markers of class-switched memory B cells and plasmablasts, whereas only few cells displayed a naïve phenotype. The frequency of tetramer-positive cells was high (up to 1/500 memory B cells with a median of 1/12 500 total B cells) and correlated with ACPA serum titres and spontaneous ACPA production in culture. Conclusions: We developed a technology to identify and isolate citrullinated antigen-specific B cells from peripheral blood of patients with RA. Most cells have a memory phenotype, express IgA or IgG and are present in relatively high frequencies. These data pave the path for a direct and detailed molecular characterisation of ACPA-expressing B cells and could lead to the identification of novel therapeutic targets.